1994
DOI: 10.1200/jco.1994.12.3.601
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of prognostic variables from patient-completed questionnaires. North Central Cancer Treatment Group.

Abstract: Data generated by a patient-completed questionnaire can provide important prognostic information independent from that obtained by other physician-determined prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
0
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(161 citation statements)
references
References 14 publications
4
151
0
6
Order By: Relevance
“…There is a burgeoning literature investigating how oncologists and patients address the benefits and risks of chemotherapy and the interpretation of prognostic information in breast cancer. [35][36][37][38][39][40][41][42][43][44][45][46] Many of these studies suggest there is needed improvement in the communication of risks and benefits from provider to patient in cancer care. When genomic technologies are determined to have clinical utility in cancer care, physicians will need to know how to communicate information about risks and benefits in ways that promote informed patient decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…There is a burgeoning literature investigating how oncologists and patients address the benefits and risks of chemotherapy and the interpretation of prognostic information in breast cancer. [35][36][37][38][39][40][41][42][43][44][45][46] Many of these studies suggest there is needed improvement in the communication of risks and benefits from provider to patient in cancer care. When genomic technologies are determined to have clinical utility in cancer care, physicians will need to know how to communicate information about risks and benefits in ways that promote informed patient decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The first and third methods took into account the different prognostic weightings whereas the second assurned equal weighting among the 6 prognostic factors. However, the nomogram requires a (84). Physicians also rated the patients' performance status.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…[1][2][3][4] More specifically, studies have suggested that such an association may exist among patients with advanced malignancies of the breast, 4 -10 esophagus, 11 colorectum, 2,12 skin (melanoma), 13,14 and lung. 2,[15][16][17][18][19][20] This trend also may occur among patients with terminal cancer 21 ; however, the magnitude and clinical relevance of these effects remain unclear. 22 Some authors have found that the presence or intensity of some physical symptoms (e.g., cognitive impairment, anorexia, xerostomia, dysphagia, and dyspnea) have independent prognostic importance in patients with a median survival of Ď˝ 2 months.…”
mentioning
confidence: 99%